Deconstructing language structure and meaning studies on syntax, semantics and phonology - Tanase-Dogaru, Mihaela; Tigău, Alina; Zamfirescu, Mihaela (Cambridge Scholars Publishing, 2021)
This volume brings together a number of researchers working on generative syntax and semantics, language acquisition and phonology to explore various theoretical frameworks, ranging from generative grammar and formal semantics to more descriptive approaches. The contributions gathered here investigate various aspects in the syntax, semantics, phonology and acquisition of Romanian in comparison with other (mainly Romance) languages. The book will be of interest to linguists who are keen on keeping up with the latest advances in the field of Romance studies, as well as those whose research bears.